Change in the Neural Response to Auditory Deviance Following Cognitive Therapy for Hallucinations in Patients With Schizophrenia - Knott, Verner; Wright, Nicola; Shah, Dhrasti; Baddeley, Ashley; Bowers, Hayley; de la Salle, Sara; Labelle, Alain (Frontiers in Psychiatry, 2020)
Adjunctive psychotherapeutic approaches recommended for patients with schizophrenia (SZ) who are fully or partially resistant to pharmacotherapy have rarely utilized biomarkers to enhance the understanding of treatment-effective mechanisms. As SZ patients with persistent auditory verbal hallucinations (AVH) frequently evidence reduced neural responsiveness to external auditory stimulation, which may impact cognitive and functional outcomes, this study examined the effects of cognitive behavioural therapy for voices (CBTv) on clinical and AVH symptoms and the sensory processing of auditory deviants as measured with the electroencephalographically-derived mismatch negativity (MMN) response. Twenty-four patients with SZ and AVH were randomly assigned to group CBTv treatment or a treatment as usual (TAU) condition. Patients in the group CBTv condition received treatment for five months while the matched control patients received TAU for the same time period, followed by five months of group CBTv. Assessments were conducted at baseline and at the end of treatment. Although not showing consistent changes in the frequency of AVHs, CBTv (vs. TAU) improved patients’ appraisal (p = 0.001) of and behavioural/emotional responses to AVHs, and increased both MMN generation (p = 0.001) and auditory cortex current density (p = 0.002) in response to tone pitch deviants. Improvements in AVH symptoms were correlated with change in pitch deviant MMN and current density in left primary auditory cortex. These findings of improved auditory information processing and symptom-response attributable to CBTv suggest potential clinical and functional benefits of psychotherapeutical approaches for patients with persistent AVHs.